27=26p-1

Simple and best practice solution for 27=26p-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 27=26p-1 equation:



27=26p-1
We move all terms to the left:
27-(26p-1)=0
We get rid of parentheses
-26p+1+27=0
We add all the numbers together, and all the variables
-26p+28=0
We move all terms containing p to the left, all other terms to the right
-26p=-28
p=-28/-26
p=1+1/13

See similar equations:

| -854t^2+64000t-150000=0 | | z÷11.4=6 | | 4=6r | | 5(x-3)+3=-12 | | 5x÷-x÷6=14 | | -854t^2+64000-150000=0 | | a+.93=1.42 | | 3(x+1)+2=x+9 | | 4-1/2a=6-a | | q^2+49q+144=0 | | -12=6(x+6)+6x | | q^2+49+144=0 | | 5(3x+6)=-14+29 | | 5x÷2-x÷6=14 | | 1/2x-3/4=2/3x+2 | | -79=-y–6y–16 | | 3(x+4)=4x+12-6 | | F(x)=3(2)^2-3(2)+1 | | 40+3x=180 | | 2/5x+1/6=3/10x+1/3 | | q^2-7q+144=0 | | -8-4(6a-3)=7(a+5) | | 1/3x=1/24=0 | | h÷7.8=2 | | 22=374/x | | x-2=-5+2x+2x | | Y=3x+4x=8 | | 2x^2-7=121 | | q^2-49q+144=0 | | -1/3y+1/14=13/42 | | 10-4x=35+x | | 3y–4y=3 |

Equations solver categories